A Bibliometric Analysis of Triptolide and the Recent Advances in Treating Non–Small Cell Lung Cancer - Yang, Quancheng; Zhai, Xuejia; Lv, Yi (Frontiers in Pharmacology, 2022)
In recent decades, natural products derived from plants and their derivatives have attracted great interest in the field of disease treatment. Triptolide is a tricyclic diterpene extracted from Tripterygium wilfordii, a traditional Chinese medicine, which has shown excellent therapeutic potential in the fields of immune inflammation and cancer treatment. In this study, 1,106 Web-of-Science-indexed manuscripts regarding triptolide published between 2011 and 2021 were analyzed, mapping cooccurrence networks of keywords and clusters using CiteSpace software. The research frontier and development trend were determined by keyword frequency and cluster analysis, which can be used to predict the future research development of triptolide. Non-small cell lung cancer (NSCLC) is most common in lung cancer patients, accounting for about 80% of all lung cancer patients. A large number of studies have shown that triptolide interferes with the initiation and progression of NSCLC by affecting a wide range of molecular targets and signaling pathways, including NF-κB MAPKs, P53, Wnt/β-catenin and microRNAs (miRNAs). This article reviews the research progress of anti-NSCLC effect of triptolide. In addition, the use of triptolide in combination therapy to enhance treatment of NSCLC and reduce toxicity was also described.